Endogenous estradiol and inflammation biomarkers: potential interacting mechanisms of obesity-related disease - Eldridge, Ronald C. (Cancer Causes Control, 2020)
PURPOSE: Disentangling the effects of endogenous estrogens and inflammation on obesity-related diseases requires a clearer understanding of how the two biological mechanisms relate to each other. METHODS: We studied 155 healthy postmenopausal women not taking menopausal hormone therapy enrolled in the Prostate Lung Colorectal and Ovarian (PLCO) screening cancer trial. From a baseline blood draw, we measured endogenous estradiol and 69 inflammation biomarkers: cytokines, chemokines, adipokines, angiogenic factors, growth factors, acute phase proteins, and soluble receptors. We evaluated the estradiol–inflammation relationship by assessing associations across different models (linear, ordinal logistic, and binary logistic) using a variety of estradiol classifications. We additionally investigated the estradiol–inflammation relationship stratified by baseline obesity status (BMI < 30 stratum and BMI > 30 stratum). RESULTS: Associations of estradiol with 7 inflammation biomarkers met p < 0.05 statistical significance in linear and ordinal models: C-reactive protein (CRP), adiponectin, chemokine (C-X-C motif) ligand-6, thymus activation-regulated chemokine, eosinophil chemotactic protein, plasminogen activator inhibitor-1, and serum amyloid A. The positive association between estradiol and CRP was robust to model changes. Each standard deviation increase in endogenous estradiol doubled a woman’s odds of having CRP levels higher than the study median (odds ratio 2.29; 95% confidence interval 1.28, 4.09). Estradiol was consistently inversely associated with adiponectin. Other estradiol–inflammation biomarker associations were not robust to model changes. CONCLUSIONS: Endogenous estradiol appears to be associated with CRP and adiponectin; the evidence is limited for other inflammation biomarkers.